Utilization of Digital Media in PAI Learning Through the Social Interaction Model Approach and Information Processing Model - Zihnil Afif; Devi Syukri Azhari (Indonesian Journal of Educational Science and Technology, 2022)
Digital media is a medium that no longer uses human or manual labor but uses machines in various fields including education. For this reason, so that the use of digital technology has a positive impact, it must be used as well as possible, for example in learning. As in the use of PAI learning by using social interaction models and information processing models. as well as the role of digital learning media or learning digital-based social interaction models in PAI learning is an effort to improve more effective learning so that learning can be more optimal and more effective.